THE TRADITION OF “UM-UMUN” AS CULTURAL IDENTITY TO PRESERVE FOOD SECURITY AMONG THE KEI SOCIETY IN OHOI LANGGUR, SOUTHEAST MALUKU - Rustam, Tata Myranti; Farid, Muhammad (Faculty of Administrative Science, Universitas Brawijaya, 2024)
Um-Umun or “Bakar Batu” is a traditional Kei cooking art that uses hot stones as a technique. This research aims to explore and document the Bakar Batu tradition in the Kei community of Southeast Maluku, especially the village of Ohoi Langgur, who generally work as farmers and fishermen. This exploratory study is important to carry out as an effort to prevent the fading of traditions and, at the same time as an effort to preserve culture and local wisdom, which can contribute to strengthening the identity of the Kei people and the treasures of cultural diversity of the archipelago. This research uses qualitative methods with documentation techniques, participant observation, in-depth interviews, and collecting oral history literature for analysis. The analysis technique uses the Creswell pattern by organizing data, interpreting, meaning and concluding. The research results show that the tradition of burning stones has implications for strengthening fraternal bonds in the form of eating together, gathering, expressing gratitude and sharing.